Navigating Curriculum Integration in Minority Contexts: Challenges and Cultural Dynamics of Integrated Islamic Education in Pattani, Thailand - Moh Dheva Syahroni Attijani; Siti Mutholingah; Rosidin Rosidin; Sella eyra (J-PAI: Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the practice of integrative Islamic education at Santi Wittya Serong Pattani Thailad School in balancing religious and national curricula, identifying challenges in its implementation and the role of Malay-Islamic culture in strengthening it. This study uses a descriptive qualitative design, with data collection through participant observation, in-depth interviews, and documentation. Data analysis uses thematic analysis techniques to identify key themes related to the integrated Islamic education curriculum, challenges in its implementation, and the influence of Malay-Islamic culture. The results reveal that (1) integrated Islamic education at Santi Wittya has been implemented by combining religious and national curricula, but it is not balanced due to the dominance of the national curriculum; (2) the main challenges lie in the limited number of human resources who are proficient in both religious and general subjects, as well as structural constraints such as the non-recognition of religious subjects in the national evaluation system; (3) Malay-Islamic culture plays a significant role in strengthening integrative education through daily rituals, the use of the Malay language, and non-formal mosque-based schools. This study has relevant contributions to models of integrative Islamic education, Muslim minority education, or culture-based critical pedagogy. Thus, integrative Islamic education based on strengthening the distinctive Malay-Islamic culture of Pattani is a novelty in this study.